Peculiarities of surgical tactics in the deep veins thrombosis of lower extremities - V. V. Boyko; V. O. Prasol; I. A. Taraban; D. V. Oklei; V. V. Shafranskyiv; S. A. Andreyeshchev (Клінічна хірургія)
Peculiarities of surgical tactics in the deep veins thrombosis of lower extremities